(untitled) (Third Sector Social Economic Review, 2026)
The aim of this study is to examine the relationship between work engagement levels and job satisfaction among tourism academics in Türkiye. The research population consists of 2338 tourism academics working in state and foundation universities in Türkiye. Data were collected from 229 academics reached through convenience sampling using the survey technique. The data were tested using Confirmatory Factor Analysis (CFA) and Path Analysis. The findings indicate that all sub-dimensions of work engagement (vigor, dedication, and absorption) were positively and significantly associated with job satisfaction. It was determined that the strongest relationship was found in the absorption dimension. The research results point out that work engagement components should be taken into consideration by higher education institutions while developing strategies aimed at increasing the job satisfaction of academic staff and, consequently, institutional productivity. In this regard, various recommendations have been presented for university administrations, policymakers, and future researchers.